Magnetic and dielectric properties of Zn substituted cobalt oxide nanoparticles. Issue 13 (September 2019) - Bindu Duvuru, H.; Alla, S.K.; Shaw, S.K.; Meena, Sher Singh; Gupta, Nidhi; Prasad, B.B.V.S. Vara; Kothawale, M.M.; Kumar, M.K.; Prasad, N.K.
Abstract: Zinc-substituted cobalt oxide nanoparticles (Znx Co3-x O4, 0 ≤  x  ≤ 0.5) were produced by microwave refluxing technique. The structural, microstructural and magnetic properties of these samples were studied using X-ray diffractometer (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM) and magnetic property measurement system (MPMS) respectively. XRD and TEM analyses confirmed the single phase nature for all the samples. Rietveld analysis of the samples further confirmed the substitution of Zn-ions into the Co3 O4 lattice. The chemical states of the elements were studied using X-ray photoelectron spectroscopy (XPS), which suggest the presence of Zn 2+, Co 2+, and Co 3+ ions in the samples. The maximum saturation magnetization (MS ) values of 0.33 Am 2 /kg was obtained for x  = 0.01 sample, and then it continuously reduced with increased Zn content. The dielectric property of the samples was studied in the frequency range of 40 Hz–110 MHz. The samples x  = 0.05 and 0.5 displayed the lowest conductivity due to the narrow size distribution of grains.